Focal Liver Lesions Classification and Characterization: What Value Do DWI and ADC Have?. Issue 5 (September 2016) - Calistri, Linda; Castellani, Alessandro; Matteuzzi, Benedetta; Mazzoni, Elisa; Pradella, Silvia; Colagrande, Stefano
Abstract : Objective: The aim of this work was to analyze the value of diffusion-weighted imaging (DWI) in the classification/characterization of focal liver lesions (FLLs). Methods: Retrospective study, approved by ethical board, of 100 proven FLLs (20 hemangiomas, 20 focal nodular hyperplasia, 20 dysplastic nodules, 20 hepatocellular carcinomas, and 20 metastases) was performed by 1.5-T MR. For each lesion, 2 readers, blinded of medical history, have evaluated 6 sets of images: set A (T1/T2-weighted images), set B (set A + DWI), set C (set B + apparent diffusion coefficient [ADC] map), set D (set A + dynamic and hepatobiliary phases), set E (set D + DWI), set F (set E + ADC map). Results: In unenhanced images, the evaluation of the ADC improves the accuracy in classification/characterization (+9%/14%, respectively), whereas in enhanced images the accuracy was increased by DWI (+7%/12%, respectively) and ADC (+13%/19%, respectively). Diffusion-weighted imaging does not improve classification/characterization of hemangiomas, may be useful in focal nodular hyperplasia/dysplastic nodules vs metastases/hepatocellular carcinoma differentiation, and increases the classification/characterization of metastases in both unenhanced and enhanced images. Conclusions: Diffusion-weighted imaging may improve classification/characterization of FLLs at unenhanced/enhanced examinations.